KUDA KEPANG BARONGAN : EKSISTENSI KEBUDAYAAN ETNIS JAWA DI PONTIANAK SEBAGAI SUMBER BELAJAR IPS - Iwan Ramadhan; Haris Firmansyah; Nur Meily Adlika; Hadi Wiyono; Astrini Eka Putri (STKIP Singkawang, 2023)
The purpose of this study was to describe the early history of the formation of the Kuda Kepang Barongan culture, the views of the community on culture and the impact and existence of the Kuda Kepang Barongan culture in Pontianak by the Margo Tresno Association, the methods used were observation, in-depth interviews with informants, the results, the traditional art of Kuda Kepang Barongan that grows and develops in Pontianak City thanks to the Margo Tresno Association is evidence of the acculturation of Javanese ethnicity in Pontianak. Obtained were early history Initially, the existence of the Kuda Kepang Barongan culture was sparked by the Margo Tresno Association which wanted to maintain the existence of Javanese ethnic culture in Pontianak. The community's view of this culture was welcomed by the artists with the presence of horse braid players who were not only from Javanese ethnicity but other ethnicities also participated. the cultural arts of the barong braid horse further enrich the culture in the city of Pontianak in particular, this is in accordance with the characteristics of the city of Pontianak which has a variety of cultures and ethnic groups which is commonly called multicultural. As a source of social studies learning, namely maintaining the existence of local wisdom culture and material for social interaction and cultural history in Pontianak.